DIRECT ISOLATION OF THE HYALINE LAYER PROTEIN RELEASED FROM THE CORTICAL GRANULES OF THE SEA URCHIN EGG AT FERTILIZATION - Kane, R. E. (The Rockefeller University Press, 1970)
Treatment of the eggs of the sea urchin with a 1 M solution of glycerol at fertilization allows the recovery from this solution of the protein released from the cortical granules, including that which would normally give rise to the hyaline layer. The calcium-gelable protein previously extracted from whole eggs and from isolated cortical material was found to be present in the glycerol solution, confirming its localization in the cortical granules and its role in the hyaline layer. Quantitative measurements on the eggs of two Hawaiian species, Colobocentrotus atratus and Pseudoboletia indiana, which have the widest variation in the gel protein content, demonstrated that a proportionate amount of this material was released at fertilization in these species, which correlates with the thickness of the hyaline layer in the two cases. In addition, the calcium-insoluble fraction of Sakai can be extracted from these eggs after removal of the hyaline protein by glycerol, showing that this is a different material. A simple method for the separation of the hyaline protein from the calcium-insoluble fraction in solution is provided.